Question

An Accountant using the expressions (4a+3b-6c) and (5a+c) to calculate the total compensation for employees in two different departments of a business.

What is the sum of the two expressions?​

Answers

  1. Answer:

    The sum of two expressions will be:

    • \left(4a+3b-6c\right)+\left(5a+c\right)=9a+3b-5c

    Step-by-step explanation:

    Given the expressions

    • (4a+3b-6c)
    • (5a+c)

    Let us calculate the sum of two expressions

    \left(4a+3b-6c\right)+\left(5a+c\right)

    Remove the parentheses: (a)=a

    =4a+3b-6c+5a+c

    Group like terms

    =4a+5a+3b-6c+c

    Add similar elements:  4a+5a=9a

    =9a+3b-6c+c

    Add similar elements:  -6c+c=-5c

    =9a+3b-5c

    Thus, the sum of two expressions will be:

    • \left(4a+3b-6c\right)+\left(5a+c\right)=9a+3b-5c

Leave a Comment